2013
DOI: 10.1371/journal.pone.0083444
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Phylogeny, Evolution and Expression Patterns of AP2/ERF Genes and Cytokinin Response Factors in Brassica rapa ssp. pekinensis

Abstract: The AP2/ERF transcription factor family is one of the largest families involved in growth and development, hormone responses, and biotic or abiotic stress responses in plants. In this study, 281 AP2/ERF transcription factor unigenes were identified in Chinese cabbage. These superfamily members were classified into three families (AP2, ERF, and RAV). The ERF family was subdivided into the DREB subfamily and the ERF subfamily with 13 groups (I– XI) based on sequence similarity. Duplication, evolution and diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 102 publications
5
41
0
Order By: Relevance
“…rapa genes belonging to different gene families or having important biological functions have been systematically analyzed. Based on the genome sequencing and comparative genomic study of B. rapa, the evolution of many gene families or categories such as circadian clock genes, 41 resistance genes, 42 stress response genes, [43][44][45] glucosinolate genes, 38 anthocyanin biosynthesis genes, 46 phytohormone-related genes, 47 certain transcript factor families 48 and other genes, [49][50][51][52][53][54] were accurately determined individually and studied in detail. Moreover, some functionally important genes related to self-incompatibility, 55,56 male sterility, 57 flowering regulation, 58-60 leaf heading 61 or color 62 have been identified or cloned, and functional studies have been conducted for some of these genes.…”
Section: Two-step Theory To Illustrate the Wgt Process Inmentioning
confidence: 99%
“…rapa genes belonging to different gene families or having important biological functions have been systematically analyzed. Based on the genome sequencing and comparative genomic study of B. rapa, the evolution of many gene families or categories such as circadian clock genes, 41 resistance genes, 42 stress response genes, [43][44][45] glucosinolate genes, 38 anthocyanin biosynthesis genes, 46 phytohormone-related genes, 47 certain transcript factor families 48 and other genes, [49][50][51][52][53][54] were accurately determined individually and studied in detail. Moreover, some functionally important genes related to self-incompatibility, 55,56 male sterility, 57 flowering regulation, 58-60 leaf heading 61 or color 62 have been identified or cloned, and functional studies have been conducted for some of these genes.…”
Section: Two-step Theory To Illustrate the Wgt Process Inmentioning
confidence: 99%
“…Most notably, Cotton_A_11454 and Cotton_A_17367, as previously mentioned, encode double-AP2/ERF domains, but clustered with subfamilies V and Xb-L in the ERF family, which usually contain genes with single-AP2/ERF domain. Liu et al (2013) also reported this discordance with Bra034249 in B. rapa, but grouped it into the AP2_2 subfamily, which contains exclusively double-AP2/ERF domains. We feel that this finding (Liu et al, 2013) is not totally convincing.…”
Section: Phylogenetic Analysismentioning
confidence: 93%
“…Liu et al (2013) also reported this discordance with Bra034249 in B. rapa, but grouped it into the AP2_2 subfamily, which contains exclusively double-AP2/ERF domains. We feel that this finding (Liu et al, 2013) is not totally convincing. Alternatively, according to the classification of Sakuma et al (2002), genes in the ERF family identified in the present study were classified into two subfamilies consisting of 163 DREB (subfamily I-IV) and 286 ERF (subfamily V-X) genes.…”
Section: Phylogenetic Analysismentioning
confidence: 93%
See 2 more Smart Citations